Managing second-growth forests as caribou habitat - Stevenson, Susan K. (Rangifer, 1990)
Habitat management for woodland caribou (Rangifer tarandus caribou) in southeastern British Columbia has generally focussed on protecting old-growth forests from logging. As that strategy becomes more difficult to maintain, biologists are beginning to explore opportunities to manage second-growth stands to provide arboreal lichens and other habitat resources important to caribou. Special harvesting and stand management practices are being developed and formulated into strategies for maintaining caribou populations in managed stands.
Keywords: woodland caribou; British Columbia; habitat management; arboreal lichens; forestry